The Role of the Women's Empowerment and Child Protection Office in Handling Violence Against Women in Mamuju Regency - Rukmana, Novayanti Sopia; Guntur, Muhammad; Alifqa, Noer Islah; Aina, Asri Nur (Universitas Negeri Makassar, 2024)
This study aims to find out how the role of the Office of Women's Empowerment and Child Protection in Handling Violence Against Women in Mamuju Regency and what supporting and inhibiting factors are faced in its optimization. This research uses a qualitative approach. Data collection is done through observation, interview, and documentation techniques. The data analysis technique used in this study is interactive data analysis through stages: data collection, data reduction, data presentation, and conclusion testing. The results of this study show that the Role of the Office of Women's Empowerment and Child Protection in Handling Violence Against Women in Mamuju Regency is seen from the results of research conducted by researchers that overall the role of DP3A has run well based on programs successfully run by DP3A such as the anti-violence campaign program carried out by DP3A by means of socialization to each village by campaigning that all forms of discrimination This should not be done especially for women and other programs such as improving gender equality by providing skills to improve welfare through trainings held by DP3A. The additional research results are supported by an assessment of several indicators and theories used, namely there are 5 indicators which include: 1. Stabilizers that have run well such as the implementation of appropriate SOPs, 2. Innovators that have not run well seen from the lack of innovation regarding violence prevention, 3. Modernizers that have not run well because they only make updates regarding the handling of cases against victims in terms of facilities and lack of updates related to prevention, 4. Pioneers that have run well based on successful collaboration with several agencies that have correlations in certain cases, 5. The implementation itself that has been running well can be seen from the many services offered to the community in order to minimize and eradicate violence against women. This is evidenced by the results of observations and interviews that have been conducted. Suggestion: The Office of Women's Empowerment and Child Protection can conduct regular socialization in an effort to identify, prevent, and handle violence against women in Mamuju Regency.